2018
DOI: 10.7717/peerj.5856
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering hidden specific diversity of Andean glassfrogs of theCentrolene buckleyispecies complex (Anura: Centrolenidae)

Abstract: The glassfrog Centrolene buckleyi has been recognized as a species complex. Herein, using coalescence-based species delimitation methods, we evaluate the specific diversity within this taxon. Four coalescence approaches (generalized mixed Yule coalescents, Bayesian general mixed Yule-coalescent, Poisson tree processes, and Bayesian Poisson tree processes) were consistent with the delimitation results, identifying four lineages within what is currently recognized as C. buckleyi. We propose three new candidate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Fouquet et al [ 38 ] proposed that a genetic distance higher than 3% in the 16Sar-16Sbr fragment could be enough to suggest the presence of unnamed species in the studied sample, and using this approach, the authors identified 129 candidate species among neotropical anurans. Although this threshold should be taken with caution, since several species have been recognized with lower genetic distance values [ 46 , 47 ], it has been helpful in several cases. The genetic divergences estimated here between the Carlos Chagas–MG population and the other specimens of Pseudis fusca from both the 16Sar-16Sbr fragment and the H1 fragment are much higher than 3%, and may indicate that the individuals from Carlos Chagas–MG represent an undescribed species.…”
Section: Discussionmentioning
confidence: 99%
“…Fouquet et al [ 38 ] proposed that a genetic distance higher than 3% in the 16Sar-16Sbr fragment could be enough to suggest the presence of unnamed species in the studied sample, and using this approach, the authors identified 129 candidate species among neotropical anurans. Although this threshold should be taken with caution, since several species have been recognized with lower genetic distance values [ 46 , 47 ], it has been helpful in several cases. The genetic divergences estimated here between the Carlos Chagas–MG population and the other specimens of Pseudis fusca from both the 16Sar-16Sbr fragment and the H1 fragment are much higher than 3%, and may indicate that the individuals from Carlos Chagas–MG represent an undescribed species.…”
Section: Discussionmentioning
confidence: 99%
“…Both localities are on the western versant of the Andes of Ecuador, on the slopes of the Cordillera Occidental. Because Centrolene buckleyi represents a species complex [20,98] (Figure 24), we here designate a neotype for Centrolene buckleyi (KU 202770, adult female) collected from Laguna de Cuicocha (near the syntype locality of Intac = Intag), thereby allowing clear comparisons among populations that might represent independent lineages. The morphological characteristics of the neotype fully correspond to those mentioned by Boulenger [93] in the original description of the species.…”
Section: Potential Distributionmentioning
confidence: 99%
“…Call (Figure 28): Two descriptions of the call of Centrolene buckleyi are available in the literature [20,100]. The differences between these calls, combined with the non-monophyly of C. buckleyi (Figure 24), clearly show that Centrolene buckleyi, as currently recognized, represents a species complex [20,98]. Below we describe a call from the highlands of Ecuador (MZUTI 763; see Examined Specimens); although the call presented herein is not from the neotype locality, genetically, it clusters together with samples from the type locality; thus, apparently corresponding to the same species.…”
Section: Potential Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a photograph, the specimen may be associated with the C. buckleyi species group ( Yánez et al 2010 ). Previous analyses of the group’s phylogenetic relationships show a high cryptic diversity in the species complex ( Amador et al 2018 ). Therefore, this could correspond to a potentially new species, though additional collections and phylogenetic analysis of these populations is necessary to determine its status.…”
Section: Species Accountsmentioning
confidence: 99%